2018
DOI: 10.1039/c8ra07119e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of sulfur-containing hybrid materials based on sodium silicate

Abstract: Hybrid Si(CH2)3SH–SBA-15 and Si(CH2)3SO3H–SBA-15 silicas were obtained with developed specific surface area and an effective pore diameter of 3.5–5.7 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…27,28,33 Previously, SBA-15 was primarily obtained using expensive tetraethyl ortho silicate as the silica precursor; therefore, an inexpensive sodium silicate as a source of silica has become an attractive option. 29,30,34 Using another source of silica than in our previous studies (i.e., solution of sodium silicate instead of solid salt) led to further characteristics of the samples especially of "bare" SBA-15. It provided particles of the nanosize that agglomerated into larger formations.…”
Section: ■ Results and Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…27,28,33 Previously, SBA-15 was primarily obtained using expensive tetraethyl ortho silicate as the silica precursor; therefore, an inexpensive sodium silicate as a source of silica has become an attractive option. 29,30,34 Using another source of silica than in our previous studies (i.e., solution of sodium silicate instead of solid salt) led to further characteristics of the samples especially of "bare" SBA-15. It provided particles of the nanosize that agglomerated into larger formations.…”
Section: ■ Results and Discussionmentioning
confidence: 80%
“…The pure SBA-15 (sample SBA ) was prepared according to previous publications with some modifications. , Briefly, 2.5 g of surfactant (Pluronic 123) was dissolved in 70 mL of 2 M HCl during constant stirring for 30 min at room temperature giving a transparent solution. 0.05 mol of SS, separately dissolved in 20 mL of water, was added in a thin stream to the resulting clear mixture.…”
Section: Methodsmentioning
confidence: 99%
“…The functionalization of the surface of mesoporous materials with organic or inorganic functional groups leads to new physical and chemical properties [45] and can enhance the adsorption capacity toward heavy metals [58]. Thus, [59] showed that among a series of adsorbents of SBA-15-type with different ligands, neat SBA-15 showed the lowest adsorption capacity toward rare earth elements and heavy metals.…”
Section: Mesoporous Materials Synthesis and Characterizationmentioning
confidence: 99%